2012
DOI: 10.1089/gyn.2011.0038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Non-Opioid Analgesics on Opioid Consumption for Postoperative Pain Relief After Abdominal Hysterectomy

Abstract: Objective: The purpose of this study was to compare the analgesic efficacy and pain intensity of and patient's satisfaction with non-opioid analgesics while evaluating postoperative piritramide consumption for providing pain relief after abdominal hysterectomy. Design: This was a randomized, double-blinded study. Materials and Methods: With the patient under general anesthesia, surgery was performed on 120 women using propofol, remifentanil, and muscle relaxant. Four patient groups (n = 30 each) were treated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 41 publications
4
48
0
1
Order By: Relevance
“…Akaraviputh et al indicated that preoperative infusion 20mg parecoxib could reduce the postoperative opioid consumption 30, and Papadima et al showed that preoperative parecoxib 40mg was efficacious for pain control and opioids sparing following laparoscopic cholecystectomy 31. In another study, parecoxib 40 mg twice daily attenuated worst pain in laparoscopic cholecystectomy32, but a latest study found that the efficacy of same medication on piritramide consumption and pain relief was weak 33. For gynecologic laparoscopies, the results of parecoxib are also contradictory 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Akaraviputh et al indicated that preoperative infusion 20mg parecoxib could reduce the postoperative opioid consumption 30, and Papadima et al showed that preoperative parecoxib 40mg was efficacious for pain control and opioids sparing following laparoscopic cholecystectomy 31. In another study, parecoxib 40 mg twice daily attenuated worst pain in laparoscopic cholecystectomy32, but a latest study found that the efficacy of same medication on piritramide consumption and pain relief was weak 33. For gynecologic laparoscopies, the results of parecoxib are also contradictory 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…37,38,39 Multimodal efforts like parenteral opioids, non-steroidal antiinflammatory drugs or local wound infiltration have been done to reduce overall pain and benefit postoperative conditions of patients undergoing laparoscopic surgeries. [40][41][42] Despite their efficacy with all parenteral medications, there are associated adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…El tema de analgesia y tiroidectomía tiene muchos aspectos que continúan en evaluación, con medidas del tipo de analgesia preventiva buscamos elaborar un protocolo de tiroidectomía ambulatoria en el corto plazo [12][13][14][15] .…”
Section: Discussionunclassified